Fruit supplementation reduces indices of exercise-induced muscle damage: a systematic review and meta-analysis. Issue 4 (3rd April 2021) - Doma, Kenji; Gahreman, Daniel; Connor, Jonathan
Abstract: This systematic review and meta-analysis examined the effects of fruit supplements on indices of muscle damage and physical performance measures following muscle-damaging exercise protocols. The PEDro scale and Cochrane's risk of bias tool was used to critically appraise each study, whilst forest plots were generated to report on standardised mean differences (SMD) and p -values. The studies employed a crossover-randomised design, or a randomised controlled placebo design, with measures compared between the supplement (SUPP) and placebo (PLA) conditions at 24 and 48 h following the muscle-damaging exercise protocols. Compared to the PLA condition, the SUPP condition exhibited significantly lower levels of indirect muscle damage markers ( p  = 0.02; I 2  = 44%), inflammatory markers ( p  = 0.03; I 2  = 45%) and oxidative stress ( p  < 0.001; I 2  = 58%), whilst antioxidant capacity was significantly increased ( p  = 0.04; I 2  = 82%) at 24 h post-exercise. The maximal isometric voluntary contraction was significantly greater for the SUPP condition than the PLA at 24 h ( p  < 0.001; I 2  = 81%) and 48 h ( p  < 0.001; 84%) post-exercise. Only a few studies reported on functional outcome measures (i.e. countermovement jump, cycling, sprint and running maximal oxygen uptake), and the findings appeared conflicting according to qualitative analyses. Fruit supplementation minimised the level of several biomarkers of muscle damage, inflammation and oxidative stress, whilst improved muscular contractility during periods of EIMD. These findings demonstrate that fruit supplements could be used as recovery strategies from strenuous exercise sessions.